GEJOLAK RESISTENSI DALAM SELF-FASHIONING LEILA S. CHUDORI: CERPEN “PARIS, JUNI 1988” - Sari Fitria (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
The purpose of this research is to reveal the subjectivity and autobiography of Chudori as a kind of resistance through a study of self-fashioning exiting in a short story “Paris, Juni 1998”. The self-fashioning study in this research is done by analyzing the text inductively and the applying Carl Thompson’s travel writing concepts. The result of this research shows that the self-fashioning in Paris, Juni 1998 is a kind of Cartesian and Janus-faced. The Cartesian indicates that Chudori’s subjectively is seen as impressive and trustworthy; mean while in Janus-faced we can see scrutiny and persona in Chudori’s autobiography. Keywords: travel writing, self-fashioning, subjectivity, autobiography. Cartesian, Janus-Faced